Bioetica, cellule staminali ed embrione umano: il pensiero religioso e laico. 3 maggio 2007 - Massimo Fagioli (Il sogno della farfalla, 2025)
In May 2007, Massimo Fagioli participated in a conference where scientists, moral philosophers and representatives of the three major monotheistic religions gathered to discuss bioethical issues, stem cells and human embryo research. In his speech, the psychiatrist proposed, in a simple yet radical manner, a research method on humanity that is free from a priori assumptions and religious conceptions. By recognizing the non-conscious mind, which forms at birth, as the fundamental characteristic of the human being, he provides a rigorous definition of the beginning of human life.